2016
DOI: 10.1080/08820538.2016.1228396
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitrectomy in the Management of Fungal Endophthalmitis

Abstract: Fungal endophthalmitis is an important cause of vision loss worldwide with a large body of literature describing the treatment of the disease. The evidence supporting the use of pars plana vitrectomy in the management of fungal endophthalmitis is largely comprised of case reports and case series and demonstrates the important role of vitrectomy surgery. Vitrectomy can improve the likelihood of establishing the diagnosis, enhance the treatment of infection by removing fungal elements in the vitreous, aid in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 77 publications
0
26
1
3
Order By: Relevance
“…We also found that fungal endophthalmitis can present with mass lesions in the anterior chamber and that fungi can hide and grow in the space behind the iris. Vitrectomy can remove fungal pathogens and toxins from the vitreous and can be combined with other intraocular procedures, such as lensectomy, the removal of an intraocular foreign body, and silicone oil tamponade [ 11 ]. The indications for lensectomy include traumatic lens opacity and purulent exudation on the lens surface [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that fungal endophthalmitis can present with mass lesions in the anterior chamber and that fungi can hide and grow in the space behind the iris. Vitrectomy can remove fungal pathogens and toxins from the vitreous and can be combined with other intraocular procedures, such as lensectomy, the removal of an intraocular foreign body, and silicone oil tamponade [ 11 ]. The indications for lensectomy include traumatic lens opacity and purulent exudation on the lens surface [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the occurrence of fungal endophthalmitis is rare, timely diagnosis and treatment is required to prevent vision impairment, including blindness (22). Treatment of fungal endophthalmitis is a challenge, as patients are often asymptomatic and the disease onset is delayed (4).…”
Section: Discussionmentioning
confidence: 99%
“…19 Fungal endoftalmiden şüpheleniliyorsa, özellikle ön kamara ve vitreus parasentez sıvısı analizi negatif ise tanı için vitrektomi düşünülebilir. 20 Olgularımızda sırasıyla kan ve idrar kültürü, vitreus örneği kültürü, kan kültürü ve vitreus örneği gram boyaması yardımıyla tanı kondu.…”
Section: Discussionunclassified
“…PPV tanıya yardımcı olurken, vitreustaki ve diğer intraoküler yapılardaki mantarları uzaklaştırarak enfeksiyöz yükünü azaltır, vitreus opasitelerini uzaklaştırarak vizyonu iyileştirir, antifungal ajanların vitreus boşluğu, retina ve koroide difüzyonunu artırır ve vitreus dokusunu uzaklaştırarak vitreoretinal traksiyonları azaltır. 16,20,30 Seröz, traksiyonel ve regmatojen RD fungal endoftalmide tanımlanmıştır ve kötü görsel prognozla ilişkilidir. 16,31 Sonuç olarak, PPV, fungal endoftalmide RD gelişimini önlemede ve geliştiyse de tedavisinde önemli rol oynar.…”
Section: Discussionunclassified
See 1 more Smart Citation